Diabetes in pregnancy: health risks and management. Issue 1028 (2nd March 2011) - Ali, Sarah; Dornhorst, Anne
Abstract : Diabetes in pregnancy is increasing and therefore it is important to raise awareness of the associated health risks to the mother, the growing fetus, and the future child. Perinatal mortality and morbidity is increased in diabetic pregnancies through increased stillbirths and congenital malformation rates. These are mainly the result of early fetal exposure to maternal hyperglycaemia. In the mother, pregnancy may lead to worsening or development of diabetic complications such as retinopathy, nephropathy, and hypoglycaemia. This review defines pregestational and gestational diabetes and the associated health risks to the growing fetus and mother. Management is discussed, focusing on clinical evidence based guidelines published by the American Diabetic Association and the UK National Institute for Health and Clinical Excellence on the management of pregnant women with pre-existing diabetes.